Control of gummy stem blight in watermelon through different management systems (Bioscience Journal, 2016)
Gummy stem blight, caused by Didymella bryoniae (Auersw.) Rehn, is a disease that affects the productivity of watermelon leading to losses exceeding 40%. This study aimed at evaluating the efficiency of different production systems in the control of watermelon gummy stem blight in order to establish effective methods to combat the disease. The following treatments were applied: conventional management, integrated management and organic production. Mineral fertilizer was applied to conventional and integrated management, whereas in organic production was used the cattle manure. There was application of fungicides and insecticides in commercial doses in conventional and integrated management, and the application was according to monitoring in integrated management. No fungicide or insecticide was applied to organic production. The disease severity was assessed by rating scale. The experimental design was randomized blocks. The severity of gummy stem blight increased substantially during fruit formation. Watermelon plants grown with integrated management showed lower levels of disease severity, while plants in organic production exhibited higher severity levels. We conclude that the management based on judicious monitoring in field is the best way to attain appropriate phytosanitary quality for the watermelon crop in Tocantins State, Brazil.